Households economically headed by women in times of expansion and crisis (1999-2012): the case of Latin American migrants in Spain - Bueno-García, Xiana; Vidal-Coso, Elena (REVISTA DE HISTORIOGRAFÍA (RevHisto), 2017)
Abstract: The arrival of flows of Latin-American females in Spain has been closely linked to the demand for domestic workers and carers. During the last period of economic expansion, a subsequent masculinization of these Latin American flows was seen, explaining the trend toward greater gender and occupational balance among these families. An economic recession followed, however, and unemployment impacted men more than it did women, as reflected in the rise in the number of women who became the sole breadwinners in their households. Using the Economically Active Population Survey, we explore the nature of these household structures, the changes in relation to the economic context, and the socio-demographic and labour market characteristics. Female-headed households are defined as those nuclear households where women are the only economic providers. The first of two hypotheses was a greater incidence of female-headed households among Latin American migrants than among households headed by exogamous and Spanish couples, irrespective of other socio-demographic characteristics. The second hypothesis predicted a greater incidence of female-headed households during the recent years of economic crisis. Furthermore, we expected this increase to have occurred in all households but to have been particularly high among Latin-Americans. The results confirm the prevalence of Latin American women as female heads of households and the adjustment within families in line with the changing Spanish socioeconomic and migratory context between 1999 to 2012. Key words: Economic female headship, international migration, economic crisis, Latin Americans, gender, Spain Resumen: La llegada de mujeres latinoamericanas a España ha estado estrechamente vinculado a la demanda de cuidadoras y trabajadoras domésticas en el mercado laboral. La posterior masculinización de los flujos de inmigración latinoamericanos durante el periodo de expansión económica explica la evolución hacia un mayor equilibrio de género y ocupacional entre estas familias. Sin embargo, con la llegada de la crisis económica, el desempleo afectó a los hombres más que a las mujeres y ello se ve reflejado en el creciente número de mujeres que se convirtieron en únicas proveedoras económicas de sus hogares. A través de la Encuesta de Población Activa exploramos cómo es la estructura de esos hogares, sus cambios a raíz del cambio de contexto económico y sus características sociodemográficas y laborales. Definimos los hogares encabezados por mujeres como aquellos hogares con núcleo en los que las mujeres son las únicas proveedoras económicas. Nuestra primera hipótesis se sustenta en la mayor incidencia de los hogares encabezados por mujeres entre los migrantes Latinoamericanos respecto a los españoles o a aquellos en los que convive una pareja mixta con mujer latinoamericana, e independientemente de otras características sociodemográficas. La segunda hipótesis predice una mayor incidencia de los hogares con jefatura femenina durante el periodo más reciente marcado por la crisis económica. Ese incremento se prevé para todos los hogares, pero se presume mayor entre los latinoamericanos. Los resultados confirman la prevalencia de las mujeres latinoamericanas como jefas de hogar y el ajuste de las familias al cambio de coyuntura socioeconómica y migratoria entre 1999 y 2012. Palabras clave: Jefatura femenina, migración internacional, crisis económica, Latinoamericanos, género, España doi: https://doi.org/10.20318/revhisto.2017.3709